The uses of Patient Reported Experience Measures in health systems: A systematic narrative review - Jamieson Gilmore, Kendall; Corazza, Ilaria; Coletta, Lucrezia; Allin, Sara (Health policy (Amsterdam), 2023)
•Many countries now have programmes collecting Patient Reported Experience Measures (PREMs).•PREMs are used as performance information at micro-, meso‑, and macro-levels in health systems.•The majority of evidence describes service-level quality improvement programmes for patient experience.•Using PREMs at macro- and meso‑levels may have an effect in stimulating micro-level actions.•There is limited impact evidence from improvement programmes on PREM scores or related outcomes. Background: Many governments have programmes collecting and reporting patient experience data, captured through Patient Reported Experience Measures (PREMs). Our study aims to capture and describe all the ways in which PREM data are used within healthcare systems, and explore the impacts of using PREMs at one level (e.g. national health system strategy) on other levels (e.g. providers). Methods: We conducted a narrative review, underpinned by a systematic search of the literature. Results: 1,711 unique entries were identified through the search process. After abstract screening, 142 articles were reviewed in full, resulting in 28 for final inclusion. A majority of papers describe uses of PREMs at the micro level, focussed on improving quality of front-line care. Meso-level uses were in quality-based financing or for performance improvement. Few macro-level uses were identified. We found limited evidence of the impact of meso‑ and macro- efforts to stimulate action to improve patient experience at the micro-level. Conclusions: PREM data are used as performance information at all levels in health systems. The use of PREM data at macro- and meso‑ levels may have an effect in stimulating action at the micro-level, but there is a lack of systematic evidence, or evaluation of these micro-level actions. Longitudinal studies would help better understand how to improve patient experience, and interfaces between PREM scores and the wider associated positive outcomes.